Everolimus with low‐dose tacrolimus in simultaneous pancreas and kidney transplantation. (1st June 2014) - Sageshima, Junichiro; Ciancio, Gaetano; Chen, Linda; Dohi, Takehiko; El‐Hinnawi, Ashraf; Paloyo, Siegfredo; Misawa, Ryosuke; Ekwenna, Obi; Yatawatta, Ashanga; Burke, George W.
Abstract The efficacy and safety of everolimus (EVR) in simultaneous pancreas and kidney transplantation (SPKT) is unclear. We retrospectively evaluated 25 consecutive SPKT recipients at our center from November 2011 to March 2013. All patients received dual induction (Thymoglobulin/basiliximab) and low‐dose tacrolimus plus corticosteroids. Nine patients who received EVR were compared with 14 patients who received enteric‐coated mycophenolate sodium (EC‐MPS); two patients who received sirolimus were excluded from the analysis. With a median follow‐up of 14 months, the pancreas graft survival rate was 100% in both groups, and the kidney graft survival rate was 100% and 93% in EVR and EC‐MPS patients, respectively. One EC‐MPS patient lost her kidney graft from proteinuric kidney disease. Another EC‐MPS patient received treatment for clinically diagnosed pancreas and kidney graft rejection. No rejection was observed in EVR patients. Serum creatinine and HbA1c levels were similar between the groups. There was no significant difference of surgical or medical complications. In conclusion, EVR seems to provide comparable short‐term outcome to EC‐MPS when combined with low‐dose tacrolimus/steroids and dual induction therapy. A larger study with a longer follow‐up is required to further assess this combination.